Thrombolysis with a recombinant plasminogen activator to treat a massive pulmonary embolus during emergency laparotomy. Issue 2 (5th November 2014) - Singh‐Kandola, Kiran; Thomas, Hannah; Phillips, Jessica; Sinha, Vikram
Summary: A previously healthy 38‐year‐old female presented with an enormous abdominal growth. Imaging confirmed a large, multiloculated left ovarian cyst. Surgery was expedited when she presented to hospital with an acute abdomen. Intraoperatively there was sudden cardiovascular collapse refractory to resuscitation with intravenous fluids and vasopressors. External cardiopulmonary resuscitation was commenced and an intraoperative transthoracic echocardiogram demonstrated a large pulmonary embolus. The patient received heparin anticoagulation without improvement and a decision was made to perform thrombolysis. The patient's condition stabilised, however postoperative intra‐abdominal haemorrhage ensued, with splenic decapsulation and a liver laceration requiring emergency splenectomy and packing respectively followed by transfer for tertiary hepatic surgical repair of the liver laceration. Remarkably, this patient recovered with no neurological or cognitive deficits.